جريمة التمويل الخفي للأحزاب السياسية في التشريع الجزائري - يحي بن سعيد; كلثوم ضيفي (My University, 2022)
Summary: A political party is a group of people who gather around a specific idea and a specific political orientation, and there must be certain conditions that are met by party members, such as respect for the principles of the November 1954 revolution, and there must be present in the party’s activity, as if it does not conflict with the system in The state and it must go through stages in establishing the party, the stage of authorizing the establishment and studying the conformity of the permit, as there are party structures such as the state office and the municipal office. Contributions and donations The legislator has also specified the amounts of donation, but in the event that the donation is exceeded, it is a hidden funding, as if it was from foreign parties from the party to buy loyalty or achieve personal interest or hidden gifts without having an inventory or mentioning it in the party’s property. And there are activities that the party can practice, and others that it has no authority in. If the party enters into them, it is funded in an indirect, secret and hidden way, after the availability of its pillars and ascertainment of its intention, and thus it has committed the crime and provides all its pillars according to Article 39 of the law Prevention of corruption. ............................ ملخص المذكرة: إن الحزب السياسي هو مجموعة من الأشخاص يلتفون حول فكرة معينة, و توجه سياسي معين, كما انه لابد من وجود شروط معينة تتوفر في اعضاء الحزب, كاحترام مبادئ ثورة أول نوفمبر 1954 كما انه لابد من وجود تتوفر في نشاط الحزب, كأن لايتعارض مع النظام في الدولة و لابد من المرور بمراحل في تأسيس الحزب مرحلة التصريح بالتأسيس و دراسة مطابقة التصريح كما ان هناك هياكل الحزب كالمكتب الولائي و المكتب البلدي .و لحسن سير الحزب لابد من وجود أمين عام للحزب لينظم عمله, و أمين مال كما انا الحزب يمول من الهيبات و الاشتراكات و التبرعات كما ان المشرع قد حدد كميات التبرع لكن في حالة تجاوز التبرع فهو تمويل خفي كأن يكون من اطراف اجنبية عن الحزب لشراء ولاء أو تحقيق مصلحة شخصية أو هيبات خفية بدون وجود جرد أو ذكرها في املاك الحزب. وهناك انشطة يمكن للحزب ممارستها, و اخرر ليست له صلاحية فيها فاذا دخل الحزب فيها فهو يتم تمويله بطريقة غير مباشرة و سرية و خفية و ذلك بعد توفر اركانها و تاكد من نيته و بذلك يكون قد أقدم علي الجريمة و توفر جميع اركانها حسب المادة 39 لقانون الوقاية من الفساد. ............................... Résumé: Un parti politique est un groupe de personnes qui se rassemblent autour d'une idée précise et d'une orientation politique précise, et certaines conditions doivent être remplies par les membres du parti, comme le respect des principes de la révolution de novembre 1954, et il doit y avoir présence dans l'activité du parti, comme s'il n'entrait pas en conflit avec le système de l'État et qu'il doit passer par des étapes de constitution du parti, celle d'autoriser la constitution et d'étudier la conformité du permis, car il existe des structures partisanes telles que le bureau d'état et le bureau municipal Cotisations et dons Le législateur a également précisé les montants des dons. mais en cas de dépassement du don, il s'agit d'un financement occulte, comme s'il s'agissait de partis étrangers du parti pour fidéliser ou acheter réaliser des intérêts personnels ou des dons cachés sans avoir d'inventaire ni le mentionner dans les biens du parti. Et il y a des activités que le parti peut pratiquer, et d'autres dans lesquelles il n'a aucune autorité. Si le parti s'y engage, il est financé de manière indirecte, secrète et cachée, après la disponibilité de ses piliers et la constatation de son intention, et ainsi il a commis le crime et fournit tous ses piliers conformément à l'article 39 de la loi Prévention de la corruption